PENGARUH CONTENT, ACCURACY DAN TIMELINESS TERHADAPKEPUASAN NASABAH PADA BANK ACEH DI KUTACANE - Riyan Baik; Desi Aramana; Sabitah (SUAN PUBLISHER, 2026)
This study aims to analyze the influence of Content, Accuracy, and Timeliness on customer satisfaction at Bank Aceh Syariah Kutacane Branch. This research employed a quantitative approach using a survey method involving 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with statistical software. The results indicate that Content, Accuracy, and Timeliness simultaneously have a positive and significant effect on customer satisfaction. Partially, Content and Timeliness show a positive and significant effect, while Accuracy does not significantly influence customer satisfaction. The adjusted R square value of 0.341 indicates that 34.1% of customer satisfaction variation can be explained by the three independent variables, while the remaining percentage is influenced by other factors outside the research model. These findings confirm that the quality of information content and the timeliness of services are dominant determinants in enhancing customer satisfaction within technology-based banking systems. Therefore, improving content quality and system responsiveness should become strategic priorities in digital banking service development